Sustainable application of recycled espresso coffee capsules: Natural composite development for a home composter product - Campos de Bomfim, Anne Shayene [UNESP]; Cornelis Voorwald, Herman Jacobus [UNESP]; Coelho de Carvalho Benini, Kelly Cristina; Magalhães de Oliveira, Daniel [UNESP]; Fernandes, Martin Ferreira [UNESP]; Hilário Cioffi, Maria Odila [UNESP] (Elsevier, 2021)
This work was based on sustainable principles by reusing the post-consumer waste espresso coffee capsules as raw material for a novelty composite, which should perform well concerning mechanical and thermal properties for a home composter product application, substituting neat polymers. Plastic components were mechanically recycled and mixed with dried coffee grounds, then 20 and 30 wt% reinforced composites with and without coupling agent were injected into specimens. Thermal analysis showed a slight reduction in degradation temperature and crystallinity of all composites regarding the neat matrix. Mechanical tests showed that composites suffered a decrease in mechanical strength and elongation, however tensile modulus and toughness are the same as the neat matrix. The coupling agent's addition caused matrix/reinforcement chemical interfacial interaction, enhancing tensile strength, and modulus. Finite element analysis showed that all composites could support stress and deformation during the product lifetime, depending on the wall's thickness. Considering mechanical and thermal properties, and environmental issues, composite with 30 wt% of natural reinforcement and no coupling agent is the best sustainable material for the home composter application.
Keywords: Coffee grounds; Home composter; Natural fiber reinforced composite; Plastic waste; Recycled polypropylene